Effect of media portrayals of removal of children's tissue on UK tumour bank. Issue 7513 (11th August 2005) - Seale, Clive; Kirk, Debbie; Tobin, Martin; Burton, Paul; Grundy, Richard; Pritchard-Jones, Kathy; Dixon-Woods, Mary
Abstract : Analysis of newspaper reporting shows how media scandals can affect scientific research, even when the research is not directly linked to the scandal